Operational decision-making in high-hazard organizations drawing a line in the sand - Hayes, Jan. (Ashgate Pub. Co., 2013)
"This book describes research on safety-related decision-making by operations supervisory personnel in three different high-hazard industries, and features a case study illustrating each: a chemical plant, a nuclear power station and an air-navigation service provider. The focus of this research is unique: those who supervise the frontline personnel and essentially provide the organizational link between senior management and minute-by-minute system operations"--Provided by publisher.